2018
DOI: 10.1371/journal.pone.0194399
|View full text |Cite
|
Sign up to set email alerts
|

Multi-color fluorescent reporter dengue viruses with improved stability for analysis of a multi-virus infection

Abstract: Reporter virus is a versatile tool to visualize and to analyze virus infections. However, for flaviviruses, it is difficult to maintain the inserted reporter genes on the viral genome, limiting its use in several studies that require homogeneous virus particles and several rounds of virus replication. Here, we showed that flanking inserted GFP genes on both sides with ribosome-skipping 2A sequences improved the stability and the consistency of their fluorescent signals for dengue-virus-serotype 2 (DENV2) repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Interestingly, however, it appears that our eGFP-and nLUC-expressing ZIKVs described in the present study showed greater levels of genetic instability than have the similar GFP-and luciferase-expressing JEVs previously developed by our laboratory [60,104]. An alternative approach commonly employed in the development of reporter-expressing flaviviruses is to place a reporter gene upstream of the viral full-length ORF, such as with WNV [109], DENV [99,[110][111][112], and ZIKV [67,86,87,97]. In all these cases, reporter-expressing flaviviruses are genetically unstable, eventually losing the ability to express the reporter gene.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, however, it appears that our eGFP-and nLUC-expressing ZIKVs described in the present study showed greater levels of genetic instability than have the similar GFP-and luciferase-expressing JEVs previously developed by our laboratory [60,104]. An alternative approach commonly employed in the development of reporter-expressing flaviviruses is to place a reporter gene upstream of the viral full-length ORF, such as with WNV [109], DENV [99,[110][111][112], and ZIKV [67,86,87,97]. In all these cases, reporter-expressing flaviviruses are genetically unstable, eventually losing the ability to express the reporter gene.…”
Section: Discussionmentioning
confidence: 58%
“…With the emergence of the new neurotropic ZIKV with its unexpected preference for infecting GSCs, a new research area for glioma virotherapy opened up [26,[28][29][30]43,44]. In regard to Flaviviridae, recombinant reporter viruses, for example, for West Nile and Dengue virus, were constructed using the original flavivirus genome as a packaging template [45,46]. Moreover, pseudotypes between yellow fever and West Nile viruses were constructed to study antibody responses against yellow fever [47].…”
Section: Discussionmentioning
confidence: 99%
“…As a rule, reporter viruses made without reducing the homology between duplicated capsids show marked instability, similar to the 3′ UTR reporter viruses [ 23 , 29 , 30 , 33 , 35 ]. On the other hand, reducing the homology increases stability, reported usually out to five passages in cell culture [ 25 , 26 , 32 , 35 ]. Case in point, Reporter WNV and JEV with no homology reduction were initially shown to be unstable.…”
Section: Timeline Of Reporter Flavivirus Designmentioning
confidence: 99%
“…The capsid duplication strategy has been successfully applied to many other flaviviruses, with slight variations giving different results in stability and utility, though addition of a reporter gene causes general attenuation in all cases [ 22 , 23 , 25 , 26 , 28 , 29 , 30 , 32 , 33 , 35 , 36 , 39 ]. As a rule, reporter viruses made without reducing the homology between duplicated capsids show marked instability, similar to the 3′ UTR reporter viruses [ 23 , 29 , 30 , 33 , 35 ]. On the other hand, reducing the homology increases stability, reported usually out to five passages in cell culture [ 25 , 26 , 32 , 35 ].…”
Section: Timeline Of Reporter Flavivirus Designmentioning
confidence: 99%
See 1 more Smart Citation